One-dimensional unsteady-state heat transfer in a window shade coated with microencapsulated phase change material - Tambago, Hyacinth Mae G.
Phase change materials (PCM) are thermal energy substances that can absorb or release a large amount of heat at a constant temperature as it undergoes phase transition. PCMs are used in a number of applications such as thermal regulation and improvement of heat transfer. Microencapsulated PCMs (MPCMs) may be incorporated in window textile and shade to reduce space cooling load requirements due to solar gain through windows. An evaluation of the thermal performance of a window shade coated with MPCM is presented by modelling the transport phenomenon in the material as one-dimensional unsteady-state heat transfer. The effect of the type of PCM, encapsulating material and thickness, type of coating, fabric properties, and PCM loading on the thermal performance may be investigated through the model. The temperature distribution in the fabric after a period of simulation time, the progression of the temperature of a fabric end, and the heat flux from the fabric to the room were generated from a proposed method of solution to the model and showed that the MPCM-coated fabric exhibits a much improved thermal resistance compared to an uncoated fabric. Only a short simulation time was considered using the proposed method, however, due to the limitation imposed by the stability condition that demands a large amount of computer memory. Another method of solution must be explored to complete the simulations and gain more useful insights to the performance of the MPCM-coated shade s thermal regulator.
Keywords: Heat storage; Heat flux